Performance of garden pea (Pisum sativum L.) genotypes for growth and yield characters at Dailekh, Karnali Province, Nepal (Nepal Agriculture Research Journal, 2023)
Fourteen garden pea genotypes (13 improved genotypes and 1 was standard released variety) were evaluated for their morpho-agronomic characters, powdery mildew (PM) disease resistant, and yield performance. The genotypes were evaluated in randomized complete block design with three replications at Horticulture Research Station (HRS), Dailekh in 2018 and 2019. The results revealed that genotypes were significantly (P